Cultural practices of resilient households: portuguese national report - Capucha, L. (2015)
The current report presents the results of the analysis of the interviews that were made by the Portuguese team within the RESCuE project. The objective of this report was to explore the data collected during fieldwork having as selective how interviewees mobilization four different types of capital - symbolic, socioeconomic, cultural and social - while also looking into how the impact crisis of the crisis over such capitals. The report is thought of as feeding the WP5 international report. As such, it aimed at presenting data in a way that facilitated comparison with data from other RESCuE countries. In doing so, we opted by emphasizes the excerpts that were either were representative of data for a large part of the sample, illustrated contrasting views of interviewees and different dimensions of relevant phenomena or representing unexpected findings to be further developed in international comparison. Therefore, analytical considerations and conclusions, while necessarily present in order to both offer a perspective and confer coherence to the selection of these excerpts, were kept to a minimum.